Sacred Texts & Sacred Figures: The Reception and Use of Inherited Traditions in Early Christian Literature - Pardee, Cambry G.; Tripp, Jeffrey M. (Brepols, 2022)
In tribute to the scholarly legacy of Edmondo F. Lupieri, in <span class=